IMPROVING SPEAKING SKILLS THROUGH THE IMPLEMENTATION OF THE COOPERATIVE MODEL OF TALKING STICK OF PPG PROGRAM IN SMPN 8 KOLAKA UTARA - Nurlaelah, Andi; Uleng, Besse; Husni, Andi; Maisanto, Antoni; Sitorus, Budianto (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
The problem in this research is whether learning with the talking stick type is cooperative model can improve students' speaking skills in SMPN 8 North Kolaka. The subjects in this study were all students of Class SMPN 8 Kolaka Utara with a total of 20 students consisting of 9 male students and 11 female students who were enrolled in the 2022/2023school year in odd semester. The focus of research is the learning process, namely by observing the process that occurs during the learning activities taking place, which includes the activities of teachers, students, and interactions of various elements involved in learning activities and students' speaking skills at obtained the end of each cycle after the implementation of the talking stick type cooperative model . This type of research is a classroom action research study consisting of two cycles, where each cycles functions of two meetings, with the stages of activities including planning, implementing, observing, and reflecting